Small Cell (Neuroendocrine) Carcinoma of the Cervix: An Analysis for 19 Cases and Literature Review - Lu, JunLing; Li, Ya; Wang, Jun (Frontiers in Cellular and Infection Microbiology, 2022)
Cervical SCNEC is a rarely and highly malignant invasive tumor. The incidence is low, less than 5% of all cervical cancers. Moreover, most patients with small cell carcinoma are interrelated with high risky HPV (more familiar HPV 18). Compared to squamous cell carcinoma or adenocarcinoma, patients are more prone to invade lymph nodes early. So the clinical manifestation is usually local or distant metastasis. We summarized the clinical features of 19 patients with cervical small cell carcinoma in the Second Affiliated Hospital of Dalian Medical University from 2012 to 2021, and retrospectively analyzed data from 1576 patients in twenty related research and more than fifty literatures in recent years.We found that multimodal treatment can indeed improve the tumor free survival (DFS), but the prognosis of patients is still very poor. For early stages, our treatment principles refer to the guidelines of SGO, international gynecological cancer Cooperation (GCIG) and NCCN. We suggest a combination with surgery, radiotherapy and chemotherapy. However, the general state of advanced patients is poor, whether they can tolerate the operation after neoadjuvant chemotherapy, whether the operation area can achieve tumor free, and whether this treatment will prolong the survival time of patients still need to be further discussed. In order to better prolong the tumor-free survival and prognosis of patients, we need to find gene changes suitable for targeted therapy, So as to complete the clinical application of these treatment methods. Further works are needed to explore more effective therapy for cervical SCNEC.